Comparative safety profiles of first-line immunotherapy regimens in advanced esophageal squamous cell carcinoma: a network meta-analysis focusing on toxicity stratification - Chen, Wei; Chen, Boyan; Hu, Chunbin; Wei, Qiance; Chen, Jiayi; Xue, Wenxin; Liu, Shui; Sun, Lichaoyue; Zhang, Lili; Fan, Shuo (Frontiers in Oncology, 2026)
BackgroundThe combination of immune checkpoint blockade and chemotherapy significantly improves survival when used as first-line treatment for advanced esophageal squamous cell carcinoma. Nonetheless, the safety profiles of various immune checkpoint inhibitor (ICI)-based combination therapies remain inadequately characterized, particularly regarding the incidence of severe adverse events (AEs) and immune-related adverse events (irAEs). The research employed a network meta-analysis to systematically evaluate and contrast the toxicity profiles across various initial ICI-driven treatments for advanced Esophageal squamous cell carcinoma (ESCC).MethodsAn extensive literature review was conducted across PubMed, EMBASE, the Cochrane Library, and Web of Science to identify RCTs evaluating first-line immunotherapy in advanced ESCC. The search included all records from each database’s inception to July 1, 2025. Primary endpoints included grade ≥3 treatment-related adverse events(grade ≥3 trAEs), any-grade irAEs, and grade ≥3 irAEs. Secondary analyses focused on organ-specific irAEs, including immune-mediated rash, hypothyroidism, hyperthyroidism, and pneumonitis. We conducted a Bayesian network meta-analysis to assess relative risks (RRs) and establish a treatment ranking based on Surface Under the Cumulative Ranking Curve (SUCRA) metrics, evaluating the comparative effectiveness of different therapeutic options. The study protocol was prospectively registered with PROSPERO (CRD420251113069).ResultsSeven randomized controlled trials involving 4,479 patients with advanced ESCC were included. In pairwise meta-analyses, ICI plus chemotherapy, compared with chemotherapy alone, increased the risk of grade ≥3 treatment-related adverse events (RR 1.08, 95% CI 1.00-1.17), any-grade irAEs (RR 2.04, 95% CI 1.71-2.44), and grade ≥3 irAEs (RR 2.75, 95% CI 1.98-3.82). Immune-chemotherapy also significantly elevated the risks of immune-mediated rash, hypothyroidism, and hyperthyroidism, whereas the increase in immune-mediated pneumonitis did not reach statistical significance. In Bayesian network meta-analyses, camrelizumab plus chemotherapy had the highest probability of being the regimen with the lowest risk of grade ≥3 trAEs(SCURA = 87.8%) and grade ≥3 irAEs(SCURA = 71.6%), while toripalimab plus chemotherapy ranked safest for any-grade irAEs(SCURA = 83.8%).ConclusionsFirst-line ICI-based regimens for advanced ESCC are associated with an increased risk of severe treatment-related and immune-related toxicities compared with chemotherapy alone, and their safety profiles differ substantially across regimens. Our SUCRA-based rankings provide a comparative overview of regimen-level toxicity that may assist clinicians in understanding relative safety trade-offs when selecting first-line therapy. These findings should be integrated with regimen-specific efficacy data, regulatory indications, PD-L1 status, comorbidities, and patient preferences, and are best interpreted as complementary safety evidence rather than stand-alone treatment recommendations.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/#myprospero, identifier CRD420251113069.